Transformasi Digital Proses Supply Chain untuk Meningkatkan Efisiensi Operasional Warehouse di Trakindo Batu Hijau Kabupaten Sumbawa Barat-NTB - Slamet Husain; Tomy Dwi Cahyono (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to empirically examine the digital transformation strategy of supply chain processes to improve warehouse operational efficiency at Trakindo Batu Hijau, West Sumbawa Regency. The mining heavy equipment industry requires high precision and speed in its supply chain, making traditional warehouse operations prone to delays and errors. This research applies a quantitative approach utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0 software. The sample consists of 125 respondents who are employees directly involved in supply chain and warehouse operations at Trakindo Batu Hijau, selected using a purposive sampling technique. The independent variables investigated include Warehouse Management System (WMS) Implementation, Internet of Things (IoT) Integration, and Big Data Analytics, while the dependent variable is Warehouse Operational Efficiency. The results reveal that all digital transformation components have a positive and significant effect on warehouse operational efficiency. Specifically, WMS implementation exerts the strongest impact, followed by IoT integration and Big Data Analytics. The R-Square value of 0.765 indicates that 76.5% of the variance in warehouse operational efficiency can be explained by these digital transformation strategies. These findings contribute to the Resource-Based View and Technology Acceptance Model by confirming that digital capabilities are critical assets for enhancing operational performance in remote mining environments. The study recommends that Trakindo Batu Hijau continues to invest in IoT infrastructure and staff training to sustain an agile and resilient supply chain ecosystem.